Estimation of Activity Energy Expenditure: Accelerometer Approach - Hyun Choi, Jee; Lee, Jeongwhan; Tai Hwang, Hyun; Pal Kim, Jong; Chan Park, Jae; Shin, Kunsoo (Conference proceedings (IEEE Engineering in Medicine and Biology Society. Conf.), 2005)
A novel algorithm estimating the calorie expenditure during physical activities is introduced. The physical activity is quantified by the integration of the accelerometer signals obtained from the 3D accelerometer fixed at the waist level of the human body. Simultaneous measurements of activity and calorie expenditure using 3D accelerometer and gas analyzer show the activity calorie expenditure increases as the activity increases with different rates depending on the type of activities (e.g., walking, running) as well as the physical characteristics of the subjects (e.g., gender, age, mass, and height). Based on the experimental data gathered from 94 subjects, we suggest a new algorithm estimating the activity calorie expenditure dependent on the demographic data of the subjects and the types of the activity